Antioxidant–free radical scavenging of flavonoid from The Leaves of Stelechocarpus burahol (Bl.) Hook f. & Th. - Sunarni, Titik; Pramono, Suwidjiyo; Asmah, Ratna (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
The activity testing of flavonoid compounds as antioxidant and as scavenger of free radical, isolated from the Stelechocarpus burahol leaves had been performed. The aqueous extract of the leaves was concentrated and then suspended in ethanol to produce ethanolic fraction. The fraction was chromatographed on several paper chromatography systems to produce isolate with chromatographic purity.The all isolated flavonoid was identified by paper chromatography system. Especially, the B4b isolate were identified further using spectrometer UV-Vis, FT-IR and ¹H-NMR. Their antioxidant activities were done by the DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging method.The all isolated flavonoid showed activity as DPPH scavenger. Among these isolate, B4b exhibited a strong free radical scavenging with an EC50 value of 6.43 μg/mL. They were identified and B4b isolate was pressumed as flavon with hydroxyl group on C-3, C-7, C-3', C-4' and methyl on C-5.Key words : Stelechocarpus burahol, flavonoid, antioxidant, DPPH